2019
DOI: 10.1002/celc.201901186
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Graphite Batteries with Flame‐Retardant Electrolyte Solutions

Abstract: Although trimethyl phosphate (TMP)‐based electrolyte solutions are effective to resist flames in non‐aqueous electrical energy storage devices, they are usually not so compatible with Li‐graphite negative electrodes. Herein, we solve this problem by increasing the concentration of LiPF6 salt in the solution. A benchmark graphite negative electrode (MCMB, mesocarbon microbeads) can deliver a capacity over 325 mAh g−1 and maintain good cyclability in a solution of 3 M LiPF6‐ethyl methyl carbonate (EMC)/TMP (7 : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…For example, graphite, [5][6][7] metal organic frameworks (MOFs) 8,9 and organic materials 10,11 have been utilized as positive electrode materials to accommodate anion. Meanwhile graphite, [12][13][14] soft-carbon, 15,16 metal 17,18 and metal oxides [19][20][21][22] have been employed for negative electrode materials. Ionic liquids, 23,24 traditional organic electrolyte solutions, 5,[25][26][27][28][29][30][31][32][33][34] concentrated aqueous solutions 35 and hybrid aqueous/non-aqueous solutions 36,37 have been applied as electrolyte solutions in DIBs.…”
mentioning
confidence: 99%
“…For example, graphite, [5][6][7] metal organic frameworks (MOFs) 8,9 and organic materials 10,11 have been utilized as positive electrode materials to accommodate anion. Meanwhile graphite, [12][13][14] soft-carbon, 15,16 metal 17,18 and metal oxides [19][20][21][22] have been employed for negative electrode materials. Ionic liquids, 23,24 traditional organic electrolyte solutions, 5,[25][26][27][28][29][30][31][32][33][34] concentrated aqueous solutions 35 and hybrid aqueous/non-aqueous solutions 36,37 have been applied as electrolyte solutions in DIBs.…”
mentioning
confidence: 99%
“…À with EMC [11,53] in the TMP/carbonate-mixed solutions, thus affecting the PF 6 À /Li + storage performance at the respective graphite cathode/anode.…”
Section: Tmp-based Mixed Flame-retardant Electrolyte Solutionsmentioning
confidence: 99%
“…K + , Mg 2+ , Ca 2+ ) into the LiPF 6 −TMP/carbonate mixed solutions could also promote Li + reversible intercalation into graphite anode because TMP was preferential to solvate the Lewis acid‐type cations leading to Li + was solvated by EC, beneficial to avoid the negative influence of TMP and form an effective SEI‐film on graphite anode. Moreover, in dual‐graphite batteries (DGBs) with graphite cathode and anode, TMP was also found to compete to solvate Li + and PF 6 − with EMC [11,53] in the TMP/carbonate‐mixed solutions, thus affecting the PF 6 − /Li + storage performance at the respective graphite cathode/anode.…”
Section: Safe Electrolyte Solutionsmentioning
confidence: 99%
“…Therefore, its solvation with ions is inevitable. It was until recent years that its coordination with cations received little attention from researchers in the community of lithium-ion batteries. On the other hand, the late application of TMP in dual-ion batteries (DIBs) started to arouse the interest in TMP-solvated anions. It is found that anions can hardly intercalate into a graphite positive electrode from TMP at ordinary conditions. This fact is likely to originate from both the steric hindrance of TMP and its relatively strong bond with anions.…”
Section: Introductionmentioning
confidence: 99%